Togo: Politics, economy and society in 2008 - Dirk Kohnert (Africa Yearbook Volume 5: Politics, Economy and Society South of the Sahara in 2008, 2009)
The formal legitimization of democratic transition in Togo in 2008 by free parliamentarian elections in October 2007 was honoured by the international donor community. Generous aid and debt relief helped the ailing economy to recover. Domestic politics were already overshadowed by the decisive presidential elections of 2010. Presidential candidates both of the ruling party and the opposition tried their best to create an image of a development-orientated impartial national leader. However, concerning the underlying fabric of informal politics, structured through decades of dictatorship of the Gnassingbé family, little has changed. – – Die formelle Legitimierung des demokratischen Übergangs in Togo im Jahr 2008 durch freie Parlamentswahlen im Oktober 2007 wurde von der internationalen Gebergemeinschaft honoriert. Großzügige Hilfe und Schuldenerlass halfen der angeschlagenen Wirtschaft, sich zu erholen. Die Innenpolitik wurde bereits von den entscheidenden Präsidentschaftswahlen des Jahres 2010 überschattet. Präsidentschaftskandidaten sowohl der Regierungspartei als auch der Opposition versuchten ihr Bestes, um das Bild eines entwicklungsorientierten, unparteiischen Staatsführers zu schaffen. An der zugrunde liegenden Struktur der informellen Politik, die durch die Jahrzehnte der Diktatur der Familie Gnassingbé geprägt wurde, hat sich jedoch wenig geändert.
Additional information: Author's version
Keywords: F35; F54; N47; Z13; 330; Togo; Africa Yearbook 2008; domestic policy; foreign affairs; socio-economic development; period under review 2008